Linestrength ratio spectroscopy as a new primary thermometer for redefined Kelvin dissemination. (1st November 2019) - Santamaria Amato, Luigi; Siciliani de Cumis, Mario; Bianco, Giuseppe; Pastore, Raffaele; Cancio Pastor, Pablo
Abstract: Experimental methods for primary thermometry, after Kelvin unit redefinition on May 2019, become based on a known value of the Boltzmann constant rather than by measuring temperature with respect to a reference point. In this frame, we propose linestrength ratio thermometry (LRT) as a candidate method for primary thermometry in the 9–700 K temperature range. Temperature accuracies at the ppm level are prospected for LRT applied to optical transitions of the CO molecule in the range 80–700 K and of a rare-earth-doped crystal in the 9–100 K one. Future implementations of this technique can contribute to measure the calibration-discrepancies in the ITS-90 metrological scale of thermodynamic temperature which can have a measurable impact in applications ranging from fundamental-physics to meteorology and climatology.